COMBINED MOLECULAR AND CHEMICAL ASSESSMENTS OF DIFFERENT CULTIVARS OF TAMARINDUS INDICA IN THAILAND - Pongsamart, S.; Sukrong, S.; Khanthapok, P.; Bhusawang, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Tamarind pulp has long been medically used as mild laxative. There are many cultivars of Tamarindus indica L., in Thailand. This study, tamarind cultivars with laxative activity was identified. Sequence of rbcL gene of each cultivar was used to correlate with chemical contents in tamarind pulps. Fruits and leaves of sweet-tamarind cultivars, “Srichomphu” and “Khanti”, and sour-tamarind “Priao-yak” were collected from Phetchabun province. Gene rbcL of “Srichomphu” and “Khanti” composed of 1,428 bp, where only part in rbcL gene 1,398 bp of “Priao-yak” was sequenced. The sequence of 1,368 bp in rbcL gene of all three cultivars were analyzed and compared with rbcL gene of T. indica (accession no.Z70160), there were 24 base-substitutions, and dendrogram was constructed using UPGMA method. Sweet-tamarind,“Srichomphu” and “Khanti”, belonging to Group I whereas sour-tamarind “Priao-yak” belonging to Group II. Organic acids, laxative active component, were determined by HPLC. The major organic acids in tamarind were tartaric, malic, citric, and oxalic acids. Tartaric acid content in each tamarind cultivar was significantly different (p<0.05), and “Priao-yak” had the highest content. Malic, citric and oxalic acids contents in sweet-tamarind, “Srichomphu” and “Khanti”, were not significantly different (p>0.05), however, these values were significantly different from those of sour-tamarind “Priao-yak”. Carbohydrate, reducing sugar, protein, and fiber contents in each tamarind cultivar were significantly different. Ash contents in sweet-tamarind, “Srichomphu” and “Khanti”, were not significantly different, but those values were higher (p<0.05) than that of sour-tamarind “Priao-yak”. Combined molecular and chemical assessments can be used to characterize and identify tamarind cultivars Acknowledgements: Faculty of Pharmaceutical Sciences and Post Graduated Research Fund, Chulalongkorn University.